Формування основ культури здоров’я як сучасна педагогічна проблема історіографічний аналіз - Козерук, Ю. В.; Горбань, А. В.; Нестеров, О. С.; Артеменко, В. В.; Кваша, Н. М.; Kozeruk, Y.; Horban, A.; Nesterov, O.; Artemenko, V.; Kvasha, N. (ЧНПУ, 2017)
UK: Стаття висвітлює одну з універсальних складових загальнолюдської культури, а саме процес формування культури здоров’я. Визнаючи важливість розуміння природи здоров’я в контексті педагогічної теорії та практики, автор звертається до сучасних досліджень феномену здоров’я в системі педагогічних знань, аналізує основні критерії, принципи, тенденції, що їх педагогічна наука виокремлює як важливі для процесу формування культури здоров’я в сучасному соціумі, розкриває базові категорії, підходи, напрацьовані педагогічною і суміжними галузями у вирішенні цього питання. EN: The article represents one of the universal components in common culture, namely the process of health culture formation and peculiarities of its demonstration in the modern pedagogical science. Nowadays the importance of studying the culture of health is connected with transformational processes, which gradually lead to domination of information technologies in all spheres of life. And it causes qualitative changes in realizing healthy lifestyle and helps to advance new demands to the culture of health. Pedagogics serves as that branch of science which accumulates all experience of the previous generations and also has all necessary potential for development of the system of formation of the culture of health that corresponds to modern needs of mankind. The author studies modern researches of the phenomenon of health in the system of pedagogical knowledge, the main criteria, the principles, tendencies, which are significant for the process of formation of the culture of health in modern society, recognizing the importance of realizing of the essence of health in the context of the pedagogical theory and practice. The methodological complexity of the process of the formation of the culture of personality’s health has also been pointed out in the article. On the one hand, we see the processes of increasing in human’s natural desire to be healthy, and on the other hand, there is impossibility or inability to resist the modern paces for public life. Analyzing pedagogical works, the author presents the broad application in a research of the problem of axiological approach that concentrates on the idea of the focuses on the priority of health in the world outlook system of person’s values and also valeological, pedagogical and sociological approaches. Moreover, modern pedagogical science offers not only some scientific approaches, but also the characteristics of the health phenomenon through cognitive, behavioral and motivational and valuable criteria. The question of the formation personal healthy position to the life continuous is the major issue of the modern pedagogics, that is the valuable actions of the child to his own physical state, and also the attitude to other people’s health. The author pays attention to such controversial questions of modern pedagogics as the role of surroundings in building up a healthy lifestyle and also development of the teacher’s valuable attitude towards his own health, the necessary conditions for physical, mental, social prosperity also.
Essential principles of health culture formation as modern pedagogical problem : historiographic analysis
Keywords: культура; здоров’я; цінність; педагогічна проблема; критерії; процес формування; culture; health; value; pedagogical problem; healthy lifestyle